TEORI DIFFERENTIAL ASSOCIATION EDWIN SUTHERLAND DALAM TINDAK PIDANA PENCURIAN RINGAN - Mubarokah, Wakhidatul; Widyawati, Anis (Cahaya Ilmu Bangsa, 2025)
Petty theft is one of the most common forms of conventional crime occurring in society and can be committed by individuals from various backgrounds. This study aims to analyze the crime of petty theft using Edwin H. Sutherland’s Differential Association Theory, which emphasizes that criminal behavior is learned through social interaction with groups that support legal violations. The research method used is normative juridical with a criminological approach, based on literature review of legal regulations, doctrines, and previous studies. The findings reveal that petty theft is not solely driven by economic factors but also by the internalization of deviant values acquired from social environments such as peers, family, or specific communities. For example, theft committed by juveniles often stems from social influences that normalize unlawful behavior. These results highlight the need for socially based crime prevention strategies through legal education, family involvement, and community-based social control.